EFEKTIFITAS METODE MODELING DALAM MENINGKATKAN KEMAMPUAN MELAKUKAN GERAKAN SHOLAT BAGI TUNANETRA - Aprilia Fitria Dwiguna (Jurnal Penelitian Pendidikan Khusus, 2014)
This research was conducted due to the problems found at UPTD PSBN “Tuah Sakato”  Kalumbuk Padang in which a kelayan with visual impairment in preparation class B had difficulties to do shalat movement. This research used single subject research approach and A-B-A design.the data of the research was analyzed  by using visual analysis of graphic. The  observasion was conducted in three sessions, the first one  was the baseline session (A1, B, A1) the persentace of the kelayan’s ability in the session was 28%, 100%, and 100%. The percentage of the data overlapped in the baseline contidion (A1) was 0%, and in the baseline condition (A2) was also 0%. Kata Kunci: anak tunanetra; melakukan gerakan shalat ; metode modeling.